2018
DOI: 10.1080/17843286.2018.1459231
|View full text |Cite
|
Sign up to set email alerts
|

Video-recording consultations for educational purposes in out-of-hours primary care: patients and physicians are willing to participate

Abstract: Background Video-recordings of consultations are used by general practitioner (GP) trainees to enable reflection on aspects of knowledge, skills and attitudes. Typically, these recordings are made during office hours in general practice, but little is known about using video-recording during out of hours (OOH) care, which is an important and distinct part of a GP's work. To be able to record consultations during OOH care (i.e. at the emergency department (ED) and at the General Practitioner Cooperative (GPC)),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We did not address the views of patients in our study. Previous studies show that the majority of patients are willing to participate in this type of study (Jepson et al, 2017;Krug et al, 2018;Themessl-Huber et al, 2008). In our study, 73% of patients consented to participate.…”
Section: Strengths and Weaknessesmentioning
confidence: 64%
See 1 more Smart Citation
“…We did not address the views of patients in our study. Previous studies show that the majority of patients are willing to participate in this type of study (Jepson et al, 2017;Krug et al, 2018;Themessl-Huber et al, 2008). In our study, 73% of patients consented to participate.…”
Section: Strengths and Weaknessesmentioning
confidence: 64%
“…As far as we know, video recording for research purposes have not yet been used in OOH primary care. In a previous questionnaire study, we learned that almost 80% of patients would consent to video recording their OOH consultation, without the physical examination on camera (Krug et al, 2018). Video recordings could give us insight into the explicit and inexplicit elements during a doctor-patient interaction, which might give us more insight into how we could facilitate these consultations to improve for example prescribing behavior of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Furthermore, a study of 323 patients in Belgium revealed that although most patients would consent to their consultations being video-recorded without physical examination, emotions of shyness or discomfort were present in 30.6 per cent of those surveyed. 11 Interestingly, the Belgian study also showed that more patients consented to their consultations being recorded if the physician was the only person being recorded. Therefore, a potential solution is to ask patients if they are comfortable with only their doctor being recorded for educational purposes, which may lessen their feelings of discomfort.…”
Section: Discussionmentioning
confidence: 99%